2018
DOI: 10.12691/wjce-6-1-10
|View full text |Cite
|
Sign up to set email alerts
|

Organic Redox-Flow Batteries Using Hair Dyes and Pharmaceuticals

Abstract: In the last few years the number of renewable energy sources (e.g. wind or solar energy) increased drastically. The availability of solar energy depends on the amount of daily sun light and the availability of electric power from wind turbines is linked to the available wind offered by nature. The increase of power from renewable energy sources has to be combined with innovative energy storage systems. Solar, wind and other renewable energy sources are intermittent energy sources. Consequently, with more renew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
1
0
2
Order By: Relevance
“…Paracetamoli st einN -Acetylderivat desp -Aminophenols. In [13] habenwir gezeigt, dass Paracetamol in alkalischerLçsung in einero rganischen Batterie zu N-acetyl-Benzochinonimin oxidiert werden kann (Abb.12).I nd er Grippostad-Batterie werden sowohl Ascorbinsäurea ls auch Paracetamolo xidiert. Im Laufev on einigenT agen wird in alkalischerL çsungd ie Acetylgruppe abgespaltenu nd dase lektrochemisch noch besser geeignetep -Aminophenol gebildet.…”
Section: Organische Batterienmit Ascorbinsäureunclassified
See 1 more Smart Citation
“…Paracetamoli st einN -Acetylderivat desp -Aminophenols. In [13] habenwir gezeigt, dass Paracetamol in alkalischerLçsung in einero rganischen Batterie zu N-acetyl-Benzochinonimin oxidiert werden kann (Abb.12).I nd er Grippostad-Batterie werden sowohl Ascorbinsäurea ls auch Paracetamolo xidiert. Im Laufev on einigenT agen wird in alkalischerL çsungd ie Acetylgruppe abgespaltenu nd dase lektrochemisch noch besser geeignetep -Aminophenol gebildet.…”
Section: Organische Batterienmit Ascorbinsäureunclassified
“…Im Laufev on einigenT agen wird in alkalischerL çsungd ie Acetylgruppe abgespaltenu nd dase lektrochemisch noch besser geeignetep -Aminophenol gebildet. Dieses kann ebenfallse lektrochemisch zu einemC hinon-imin umgesetzt werden [13].…”
Section: Organische Batterienmit Ascorbinsäureunclassified
“…Therefore, some simple settings and several organic substances are given for the demonstration of the principle of Redox-Flow-Cells in the following article. In our previous communications [14,15,16,17] we showed that Alizarin, Gallic acid, Henna red, Paracetamol and many more can be used as anodic material for organic batteries. Green tea and the flavoring substance Vanillin can be likewise electrochemically oxidized [18,19].…”
Section: Introductionmentioning
confidence: 99%